Sintomatología musculo esquelética y nivel de riesgo postural de las posiciones adoptadas por los estudiantes durante la práctica odontológica en la universidad Antonio Nariño sede Neiva (2022)
Introduction: During the practice of the profession, dentists are constantly subjected to the risk of suffering musculoskeletal disorders due to the need to maintain postures that allow them to perform precise, precise movements. Objective: To identify the level of performance of the REBA method and its relationship with musculoskeletal disorders in students and teachers of the UAN Neiva dentistry program. Materials and methods: Observational, descriptive, cross sectional and prospective study of 25 dental students to whom the Nordic and REBA questionnaires were applied to identify musculoskeletal injuries and postural risks. Results: there is a statistically significant difference between the cause of the appearance of musculoskeletal discomfort and the lev el of risk resulting from the postures evaluated in the REBA method given by a p= 0.001. Conclusions: mitigation actions should be carried out in populations with a high risk level.